2019
DOI: 10.24193/subbchem.2019.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Chemical stabilization of fats rich in long chain polyunsaturated fatty acids by antioxidants addition

Abstract: The research was conducted in order to evaluate the effect of natural (β-carotene and ascorbic acid) antioxidants on the oxidative stability of alimentary chicken fat in order to improve its safety and extend the shelf life. Peroxide value was significantly influenced by the storage time (p < 0.001) in chicken fat and 0.01% additivated fat. In control was found the highest level of peroxide value followed by 0.01% and 0.05% additivated fat. Regardless of the type of fat, the highest peroxide index level was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…As a result of the study, they reported that the combination of both applications played an effective role in the increase of carotenoids. ß-carotene is an organic red-orange colored pigment that is abundant in plants (Pop et al, 2019). Sadi et al (2017) in their study to determine the biochemical characterization of 4 (Avangard, Bony Doon, Linda and Linton) linseed varieties (phenolics, flavonoids, β-carotene, lycopene, DPPH radical capture activity, MDA, proline, SOD, CAT, APx, and GR) reported that they determined to be high.…”
Section: Biochemical Characteristicsmentioning
confidence: 99%
“…As a result of the study, they reported that the combination of both applications played an effective role in the increase of carotenoids. ß-carotene is an organic red-orange colored pigment that is abundant in plants (Pop et al, 2019). Sadi et al (2017) in their study to determine the biochemical characterization of 4 (Avangard, Bony Doon, Linda and Linton) linseed varieties (phenolics, flavonoids, β-carotene, lycopene, DPPH radical capture activity, MDA, proline, SOD, CAT, APx, and GR) reported that they determined to be high.…”
Section: Biochemical Characteristicsmentioning
confidence: 99%